2012
DOI: 10.1161/strokeaha.112.657254
|View full text |Cite
|
Sign up to set email alerts
|

Cerecyte Coil Trial

Abstract: Background and Purpose-We report the primary outcome of the Cerecyte Coil Trial, a randomized trial to determine whether polymer-loaded Cerecyte coils compared with Micrus bare platinum coils improved the proportion of patients with angiographic occlusion of the aneurysm at 6 months when assessed by a core laboratory. The secondary objectives were to compare the clinical outcomes and retreatment rates in the 2 groups. Methods-Five hundred patients between 18 and 70 years of age with a ruptured or unruptured ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 15 publications
2
43
0
2
Order By: Relevance
“…The Cerecyte trial reported a combined success rate, defined as stable angiographically visible occlusion, stable neck remnant, or improved occlusion of the aneurysm, of 57% (245/433) for ruptured and unruptured aneurysms at the 6-month follow-up. 7 The hydrogel-coated coils versus bare platinum coils for the endovascular treatment of intracranial aneurysms (HELPS) trial reported a major angiographically confirmed recurrence in 24%-33% of patients at the 18-month follow-up in a per-protocol analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The Cerecyte trial reported a combined success rate, defined as stable angiographically visible occlusion, stable neck remnant, or improved occlusion of the aneurysm, of 57% (245/433) for ruptured and unruptured aneurysms at the 6-month follow-up. 7 The hydrogel-coated coils versus bare platinum coils for the endovascular treatment of intracranial aneurysms (HELPS) trial reported a major angiographically confirmed recurrence in 24%-33% of patients at the 18-month follow-up in a per-protocol analysis.…”
Section: Discussionmentioning
confidence: 99%
“…15 Recurrent aneurysms after platinum coiling are at high risk of re-recurring when retreated, but these patients were excluded from all published randomized trials. 8,14,[16][17][18] The Patients Prone to Recurrence After Endovascular Treatment (PRET) study was designed in 2007 to offer an alternative to platinum coiling in patients previously shown to be at high risk of recurrence: patients with large (Ն10 mm) or recurrent aneurysms after coiling. The trial protocol was published in 2008.…”
mentioning
confidence: 99%
“…1 Clinical trials for other modified coils, such as the Matrix (Stryker, Kalamazoo, Michigan) and Cerecyte coils, failed to show any significant benefit for polyglycolic acid/polyglycolic/polylactic acid-modified versus bare platinum coils. 11,25 Our data suggest that hydrogel-modified coils are more beneficial in certain subsets of patients and aneurysms; recurrence rates were reduced 17%-18% in patients with an aneurysm with a small D/N or an irregularly shaped aneurysm. Our study had several limitations.…”
Section: Discussionmentioning
confidence: 76%